(untitled) (Ticontre. Teoria Testo Traduzione, 2025)
Drawing on research at the intersection of memory studies and narrative theory, this article explores multiperspectivity as a storytelling mode particularly well-suited to engaging with representations of collective memory in contemporary fiction. While often celebrated as a narrative strategy that fosters perspective-awareness and enables counter-narrativity, I argue that multiperspective storytelling must move beyond simplistic dichotomies to effectively convey a multidirectional understanding of collective memory. Building on concepts such as postmemory and the implicated subject, I then introduce the notion of pseudo-multiperspectivity to examine both the potential and risks inherent in the proliferation of characters’ perspectives and memories. Prendendo le mosse dall’intersezione di memory studies e teoria della narrazione, l’articolo esamina il multiprospettivismo come strategia narrativa particolarmente adatta ad affrontare le complessità della memoria collettiva nella narrativa contemporanea. Sebbene il multiprospettivismo sia spesso considerato come una strategia formale in grado di contrastare forme narrative dominanti, il contributo cerca di mostrare come le narrazioni multiprospettiche debbano andare oltre facili dicotomie per offrire una comprensione multidirezionale della memoria collettiva. Prendendo ispirazione da concetti quali post-memoria e soggetto implicato, propongo quindi la nozione di pseudo-multiprospettivismo per esplorare le potenzialità e i rischi della moltiplicazione delle prospettive e dei ricordi dei personaggi finzionali.